2018
DOI: 10.3390/app8112274
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Blended Biochar Pellet by the Use of Nutrient Releasing Model

Abstract: For the recycling of biomass conversion materials, this experiment was conducted to investigate plant nutrient releasing characteristics, and to determine an optimum blended ratio of biochar for producing a biochar pellet based on a column leaching study. The treatments consisted of only pig manure compost (PMC) as a control, pig manure compost pellets (PMCP), and biochar pellets (BCP) blended with biochar and pig manure compost with the following ratios: 9:1, 8:2, 4:6, and 2:8. Results showed that the accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
0
8
0
4
Order By: Relevance
“…The loss of labile aliphatic compounds in biochar samples derived from pig manure, crop residues, and municipal solid waste has been reported to cause the disappearance of hydrophobicity when the pyrolysis temperature is over 500 °C [53]. Omondi et al showed in their review that for a Other studies have also reported that biochar produced from cellulosic biomass such as grain husk [14], pig manure compost [45,46], cattle manure [47], cattle manure mixed with straw [47], chicken manure [47], chicken manure mixed with sawdust [47] and pig slurry (PC) [47], red oak (Quercus rubra) [15,22], ground wheat straw and wood pellets (69% Norway Spruce, 19% Beech plus other wood species) [25], North European grassland species [34], Picea abies (70%) and deciduous wood shavings of Fagus sylvatica (30%) [27], wheat and maize straws [33], mesquite feedstock/mesquite wood (Prosopis sp.) [32,48], and Pseudotsuga menziesii [24] have large portions of the volume of pores that are 1 (or smaller) to 10 µm in diameter, because the biochar inherited the architecture of the biomass [9,[48][49][50].…”
Section: Hydrophobicity Of Biocharmentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of labile aliphatic compounds in biochar samples derived from pig manure, crop residues, and municipal solid waste has been reported to cause the disappearance of hydrophobicity when the pyrolysis temperature is over 500 °C [53]. Omondi et al showed in their review that for a Other studies have also reported that biochar produced from cellulosic biomass such as grain husk [14], pig manure compost [45,46], cattle manure [47], cattle manure mixed with straw [47], chicken manure [47], chicken manure mixed with sawdust [47] and pig slurry (PC) [47], red oak (Quercus rubra) [15,22], ground wheat straw and wood pellets (69% Norway Spruce, 19% Beech plus other wood species) [25], North European grassland species [34], Picea abies (70%) and deciduous wood shavings of Fagus sylvatica (30%) [27], wheat and maize straws [33], mesquite feedstock/mesquite wood (Prosopis sp.) [32,48], and Pseudotsuga menziesii [24] have large portions of the volume of pores that are 1 (or smaller) to 10 µm in diameter, because the biochar inherited the architecture of the biomass [9,[48][49][50].…”
Section: Hydrophobicity Of Biocharmentioning
confidence: 99%
“…The drawbacks of fine particulate biochar are significant weight loss of biochar during handling and transport to fields and potential chronic damage to the human respiration system [57][58][59]. Densified biochar pellets were then developed to alleviate the loss of fine biochar particles and reduce the costs of storage, transport, and handling [17,45,46,61,62]. Moreover, biochar pellets can function as a nutrient carrier to increase nutrient use efficiency by reducing the nutrient release rate.…”
Section: New Nutrient-rich Biochar Pelletsmentioning
confidence: 99%
“…‡ TN: Total nitrogen. § TC: Total carbon.25%가량은 집중 호우 시 유거수에 의해 손실된다(Shin and Park, 2018). 특히 시비할 때 비산에 의해 사람의 코나 입 으로 들어가게 되면 호흡기 관련 문제를 일으키는 단점도 있다(Shin and Park, 2018).…”
unclassified
“…§ TC: Total carbon.25%가량은 집중 호우 시 유거수에 의해 손실된다(Shin and Park, 2018). 특히 시비할 때 비산에 의해 사람의 코나 입 으로 들어가게 되면 호흡기 관련 문제를 일으키는 단점도 있다(Shin and Park, 2018). 이러한 문제점에 대해 돈분 퇴 비와 바이오차를 혼합하여 만든 돈분 바이오차 펠렛 형태는 바람에 의한 손실을 줄일 뿐만 아니라, 돈분 퇴비보다 펠 렛형 돈분 퇴비가 NH 4 + -N를 더 천천히 용출 시킨다고 하였다.…”
unclassified
See 1 more Smart Citation